The combined clinical impact of red blood cell distribution width and vascular calcification on cardiovascular events and mortality in patients with end-stage kidney disease - Da Won Kim; Munpyo Lee; Kwon Jae Lee; Yeon Hee Lee; Dongryul Kim; Seok Joon Shin; Hye Eun Yoon (The Korean Society of Nephrology, 2022)
Background Little is known about how the interaction between red blood cell distribution width (RDW) and vascular calcification (VC) affects cardiovascular (CV) events and mortality in end-stage kidney disease (ESKD) patients. This study investigated the combined prognostic effect of RDW and VC in ESKD patients starting dialysis. Methods A retrospective single-center study of 582 ESKD patients was conducted. VC was assessed by calculating the aortic calcification index (ACI) using computed tomography. Patients were divided into low ACI-low RDW, low ACI-high RDW, high ACI-low RDW, and high ACI-high RDW groups based on median ACI (17.12) and RDW (14.3) values. The association between RDW and VC and the composite endpoint of CV events and death was analyzed. Results During a median follow-up of 3.1 years (range, 1.5-5.5 years), 165 CV events (28.4%) and 124 deaths (21.4%) occurred. Cox regression showed that the low ACI-high RDW (adjusted hazard ratio [HR], 1.66; 95% confidence interval [CI], 1.04-2.66; p = 0.03) and high ACI-low RDW (adjusted HR, 1.95; 95% CI, 1.21-3.14; p = 0.006) groups had a greater risk of CV events and death than the low ACI-low RDW group. The high ACI-high RDW group had the greatest risk (adjusted HR, 2.23; 95% CI, 1.42-3.52; p = 0.001). The effect of the interaction between ACI and RDW on CV events and mortality was statistically significant (p = 0.005). Conclusion High RDW and VC interact to increase the risk of CV events and death in ESKD patients.